Neck circumference associated with arterial blood pressures and hypertension: A cross-sectional community-based study in northern Han Chinese - Fan, Shujun (Sci Rep, 2017)
Although several studies have investigated the associations of neck circumference (NC) with arterial blood pressures (BPs) and hypertension, no such studies have been conducted among Northern Chinese population. Between April and June 2015, a total of 2631 subjects aged ≥35 years old were recruited from Northeastern China. NC and arterial BPs were measured by trained personnel. Generalized linear and logistic regression analyses were applied to examine the associations of NC with arterial BPs and hypertension risk. The optimal cut-off points of NC for predicting hypertension were assessed by the receiver operating characteristic analysis. We found that NC was significantly associated with arterial BPs and hypertension risk in the Northeastern Chinese adults, even after adjusting for many covariates including body mass index, waist circumference or waist-to-hip ratio. The optimal cut-off values for NC to predict hypertension differed with sex, age, and body mass index. Our study suggests that NC may play an independent role in predicting hypertension beyond the classical anthropometric indices, and that it could be used as a valuable anthropometric measurement for routine assessment in primary care clinics and future epidemiological studies.